Designing multispecies role-playing games: From human-nature partnerships towards multispecies justice - Philip Harms; Neelakshi Joshi; Stefan Knauß (npj Urban Sustainability)
Abstract Current global socioecological crises are rooted in an anthropocentric worldview that sees humans as separate from and superior to the rest of nature. Urban sustainability planning is also anthropocentric in that it often regards non-human species as mere service providers. While anthropocentric approaches to planning are called into question, there is currently a lack of methods for incorporating more-than-human voices into planning. This paper presents multispecies role-playing games as a method of engaging with urban planning from a more-than-human perspective. First, we show how to design multispecies role-playing games based on human-nature partnership ethics. Second, we present how a multispecies justice lens can help to improve the design and application of such games in urban sustainability planning. Our findings suggest that multispecies role-playing games are a valuable method for applying ideas of multispecies justice in urban planning education, practice and research.